การจัดกระบวนการลอจิสติกส์แบบใหม่ในอุตสาหกรรมอาหารทะเลแช่แข็ง (THE MODERN LOGISTICS MANAGEMENT PROCESS IN FROZEN SEA FOOD INDUSTRY) - จุลิรัชนีกร เสาวณี (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2015)
การวิจัยมีวัตถุประสงค์เพื่อศึกษาการจัดกระบวนการลอจิสติกส์แบบใหม่และต้นทุนลอจิสติกส์ รวมทั้งการลดต้นทุนลอจิสติกส์และการใช้เทคโนโลยีสารสนเทศสำหรับระบบลอจิสติกส์ในอุตสาหกรรมอาหารทะเลแช่แข็ง กลุ่มตัวอย่างที่ใช้ในการศึกษาเป็นผู้ประกอบการผลิตอาหารทะเลแช่แข็งในภาคใต้ จำนวน 16 โรงงาน เครื่องมือในการวิจัยเป็นแบบสอบถามและการสัมภาษณ์เชิงลึก ผลการวิจัยพบว่า การจัดกระบวนการลอจิสติกส์แบบใหม่ในอุตสาหกรรมอาหารทะเลแช่แข็งต้องเป็นแบบบูรณาการในกิจกรรมหลัก 5 ด้านและการนำเทคโนโลยีสารสนเทศมาใช้ ซึ่งประกอบด้วย 1) การปฏิบัติด้านการผลิตในส่วนของการจัดหาจัดซื้อวัตถุดิบ ให้เหมาะสมกับปริมาณการผลิต และการควบคุมคุณภาพของวัตถุดิบและสินค้า 2) การขนส่งต้องมีความหลากหลายในวิธีการขนส่ง 3) คลังสินค้าต้องมีการใช้พื้นที่ของคลังให้คุ้มค่า 4) การวางแผนคำสั่งซื้อสินค้าคงคลังให้มีปริมาณพอเหมาะ 5) การเก็บรักษาสินค้าภายใต้อุณหภูมิที่เหมาะสม และผลวิจัยด้านต้นทุนลอจิสติกส์ของอาหารทะเลแช่แข็งอยู่ที่ระดับ 8.63% ต่อยอดขาย ซึ่งต่ำกว่าต้นทุนลอจิสติกส์ในอุตสาหกรรมการผลิต แต่สูงกว่าต้นทุนลอจิสติกส์ในอุตสาหกรรมอาหาร และพบว่าต้นทุนลอจิสติกส์ของอาหารทะเลแช่แข็งในธุรกิจขนาดใหญ่จะมีต้นทุนต่ำกว่าในธุรกิจขนาดเล็กและขนาดกลาง ส่วนการลดต้นทุนลอจิสติกส์นั้นผู้ประกอบการอาหารทะเลแช่แข็งต้องลดความสูญเสียที่เกิดจากสินค้าคงคลังที่มีมากเกินความจำเป็น ลดการสูญเสียจากพื้นที่ของคลังที่ใช้ประโยชน์ไม่คุ้ม และลดการสูญเสียในระบบการขนส่ง สำหรับการใช้เทคโนโลยีสารสนเทศในระดับพื้นฐานพบว่า นำมาใช้งานกับธุรกิจอาหารทะเลแช่แข็งทั้งขนาดเล็กขนาดกลางและขนาดใหญ่ ส่วนการใช้เทคโนโลยีสารสนเทศในระดับสนับสนุนการตัดสินใจนำมาใช้กับผู้ประกอบการผลิตที่มีขนาดใหญ่เท่านั้น คำสำคัญ: การจัดกระบวนการ ลอจิสติกส์แบบใหม่ อุตสาหกรรมอาหารทะเลแช่แข็ง ต้นทุนลอจิสติกส์ เทคโนโลยีสารสนเทศ The purpose of the research was to examine the organizing of new techniques for logistics processing in frozen seafood industry. A total logistic costs and logistics cost reduction and its application of information technology for logistics system in frozen seafood industry was included in the study. The research methodology employee based on a sample size of 16 manufacturing firms in Southern Thailand. The research tool were a structured questionnaire and in-depth interview. The research findings revealed that the organizing of new logistic processing in frozen seafood industry must integrate five basic activities consisting of (1) production operation must consider the raw material procurement system to be in line with production output quantity. Raw material and product quality control should be included in the operation; (2) combined transport or intermodal transport system must be considered; (3) the awareness of fully utilization of warehouse/cold storage; (4) order planning and inventory control should be maintained at optimum level; and (5) finished products must be kept at industrial standard temperature. The logistics costs of seafood industry was at 8.63% of sale volume, which was lower than production industry, but higher than food industry, and the logistics costs of seafood industry in large size was lower than in small and medium size. The frozen seafood must find way and means of lost space reduction of its warehouse and achieving full utilization, monitoring of any loss during goods in transit and transport chain. The application of information technology found in the small and medium enterprises as well in large scale industry, however, information technology decision-making was practice in large industry only. Keywords: Management process, Modern logistic management, frozen seafood industry, Logistic costs, Information technology